EFEKTIVITAS PESAN POSTER #BUDAYABEBERES DALAM MENGEDUKASI PERILAKU HIDUP BERSIH KONSUMEN KFC DI KOTA PALU - Ayu Berlian Triulandari (Kinesik, 2021)
A media can be an intermediary that supports the effectiveness of a message. Messages can be proclaimed to be effective if the communicant gives feedback as expected by the communicator. This research attempts to define the effectiveness of the #Budayabeberes massage in the poster for educating the clean living behavior of KFC consumers in Palu City. The research uses a questionnaire as a data assembly technique. The research method adopted is a quantitative method with a survey research type to describe or exemplify the topic whose findings can be generalized in this research. The subjects in this research amounted to 80 people who were selected using the purposive sampling technique with the #budayabeberes message in the poster for educating consumers to live clean life as an object of the research. The findings confirmed that the #Budayabeberes massage in the poster was effective in persuading consumers to conduct a clean-up after eating. This can be distinguished based on the theory of message effectiveness according to Wilbur Schramm which contains 4 indicators, i.e. attracting attention, symbols that are understood, constructing needs and how to retrieve. Cultivated data recapitulation of respondent’s answers with a total score of 257 so that when discerned based on the ideal score and the answer area in the rating scale, the #BudayaBeberes message in the poster is in the effective category.